LXW7 ameliorates focal cerebral ischemia injury and attenuates inflammatory responses in activated microglia in rats - Fang,T. (2016)
Inflammation plays a pivotal role in ischemic stroke, when activated microglia release excessive pro-inflammatory mediators. The inhibition of integrin αvβ3 improves outcomes in rat focal cerebral ischemia models. However, the mechanisms by which microglia are neuroprotective remain unclear. This study evaluated whether post-ischemic treatment with another integrin αvβ3 inhibitor, the cyclic arginine-glycine-aspartic acid (RGD) peptide-cGRGDdvc (LXW7), alleviates cerebral ischemic injury. The anti-inflammatory effect of LXW7 in activated microglia within rat focal cerebral ischemia models was examined. A total of 108 Sprague-Dawley rats (250–280 g) were subjected to middle cerebral artery occlusion (MCAO). After 2 h, the rats were given an intravenous injection of LXW7 (100 μg/kg) or phosphate-buffered saline (PBS). Neurological scores, infarct volumes, brain water content (BWC) and histology alterations were determined. The expressions of pro-inflammatory cytokines [tumor necrosis factor-alpha (TNF-α) and interleukin-1 beta (IL-1β)], and Iba1-positive activated microglia, within peri-ischemic brain tissue, were assessed with ELISA, western blot and immunofluorescence staining. Infarct volumes and BWC were significantly lower in LXW7-treated rats compared to those in the MCAO + PBS (control) group. The LXW7 treatment lowered the expression of pro-inflammatory cytokines. There was a reduction of Iba1-positive activated microglia, and the TNF-α and IL-1β expressions were attenuated. However, there was no difference in the Zea Longa scores between the ischemia and LXW7 groups. The results suggest that LXW7 protected against focal cerebral ischemia and attenuated inflammation in activated microglia. LXW7 may be neuroprotective during acute MCAO-induced brain damage and microglia-related neurodegenerative diseases.